(3GdfGSN hGdefShN aj GdbQBfs - (3eMeO Hf ESeGYjd GdeUaGQs
(3ChdgG (B:s
(3bGd CHh LYaQ CMeO Hf eMeO Hf eMeO GSeGYjd GdeUaGQ GdeUfa GdfMhi QMeI Gddg Ydjge CLeYjf s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs